Comparison of Methods for Analyzing Global Positioning System and Accelerometer Data during School Recess. Issue 1 (2nd January 2019) - Clevenger, Kimberly Ann; Sinha, Gaurav; Howe, Cheryl A.
ABSTRACT: Several geospatial approaches have been used to characterize physical activity during recess using global positioning system (GPS) data. GPS and accelerometer data from 23 children collected during recess were analyzed using four previously used approaches: (1) dot map, (2) fishnet grid, (3) hot spot analysis, which determines clusters of high/low intensity values, and (4) zonal approach wherein the schoolyard was divided into zones to determine the time and intensity in each zone. Results from each method were compared to each other and to video observation. Hot spot analysis revealed clusters of high-intensity values, which were supported by dot and grid maps and video. However, the zonal approach revealedpatterns in where children play that were not always comparable tovideo, potentially due to missing GPS data. Recommendations for the use of these methods in future research are discussed.